The quality of dental radiography in the Czech Republic--results of a TLD and film postal audit - Novák, Leoš (Radiation protection dosimetry, 2006)
Since 2002, the postal audit in dental radiography has been supplementing standard quality control (QC) tools for dental intraoral X-ray machines. An aim of the audit is to check basic X-ray machine parameters (field size, exposure reproducibility), and a quality of the whole process of diagnostic imaging (entrance surface air-kerma measurement, a check of film processing and an image quality evaluation). The standard QC tests, performed by private companies, check mainly the X-ray unit. Conversely, the audit gives better information about the patient examination practices. During the period of January 2002 to May 2004 approximately 4000 audits were performed. The results confirmed that main problems in dental radiography are due to incorrect film processing, non-optimised setting of the exposure parameters and use of obsolete X-ray machines. Only approximately 30% of performed audits were satisfactory with respect to all checked parameters.
Keywords: rentgendiagnostika zubní; filmová dozimetrie; lékařská praxe - způsoby provádění; Česká republika; Film Dosimetry; Quality Assurance, Health Care; průzkumy a dotazníky; Dental Audit; Radiography, Dental; zajištění kvality zdravotní péče; směrnice pro lékařskou praxi jako téma; termoluminiscenční dozimetrie; Surveys and Questionnaires; Czech Republic; Practice Guidelines as Topic; Thermoluminescent Dosimetry; Practice Patterns, Physicians'; dentální audit